Peran Kualitas Pelayanan Terhadap Loyalitas Pelanggan Jasa Transportasi Online - Ingga Widi Aprilla; Sholihati Amalia (Jurnal Riset Bisnis dan Investasi, 2019)
Service quality is a form of activity undertaken by a company that aims to meet the wants and needs of customers by providing good service. Customer loyalty is a consumer's assessment of the quality of the product or service it receives based on existing expectations in the mind. Loyal customers will always tend to only one brand even though there are many similar brands. Sample in this study amounted to 135 respondents, is the people of Bandung who have or often use online transportation. The sampling technique using simple random sampling. The purpose of this study is to find out the influence of service quality on online transportation customer loyalty. The result obtained shows that service quality influence significantly customer loyalty by 24,1%.